Study of cross-referrals to the dermatology department in an inpatient setting at a tertiary care centre - Bakhtar, Niyati; Pandey, Kirit; Pandey, Neha; Bakhtar, Nikhil; Bakhtar, Vijay (International Journal of Research in Medical Sciences, 2020)
Background: Till recently, dermatology was primarily being considered to be an outpatient focused discipline. However, several inpatient admissions to other specialties require dermatologic consultation for optimum management. This study was conducted to analyse the incidence and indications for inpatient dermatology referrals and the impact of dermatology consultation on patient management. Methods: A cross-sectional study was undertaken by analyzing the records of 243 patients referred to dermatology department over a 2-year period. Descriptive analysis was conducted in the form of study of presumptive diagnoses by the referring clinicians, causes of referral, distribution of referrals across specialties and the dermatological opinions with respect to diagnosis and management etc. Results: Clinically significant change was documented in the course of skin lesions management of almost two-thirds of referred patients. Maximum referrals were from the department of general medicine with “skin rash” being the most common cause for seeking 2nd opinion. Concordance for diagnosis between the referring clinician and the dermatologist was observed in only 30.2% of the cases. Conclusions: Dermatologic referral does lead to improved patient care. But there is need for better training of non-dermatologists enabling them to recognize and treat common skin lesions.